2023
DOI: 10.3390/ph16040565
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Anxiety and Depression: Unveiling the Relationships and Management Options

Abstract: The gut microbiota is critical for maintaining human health and the immunological system. Several neuroscientific studies have shown the significance of microbiota in developing brain systems. The gut microbiota and the brain are interconnected in a bidirectional relationship, as research on the microbiome–gut–brain axis shows. Significant evidence links anxiety and depression disorders to the community of microbes that live in the gastrointestinal system. Modified diet, fish and omega-3 fatty acid intake, mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 261 publications
0
22
0
Order By: Relevance
“…Studies have demonstrated that gut bacteria can produce neurotransmitters and other signaling chemicals that affect brain function and development ( Morais et al, 2020 ; Chen et al, 2021 ). Recent studies detailed the associations between GM, mental health, and psychological diseases and disorders including anxiety and depression ( Kumar et al, 2023 ). Genetics, nutrition, environment, and early life experiences play a role in mental health and development via GM.…”
Section: Gut-brain Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that gut bacteria can produce neurotransmitters and other signaling chemicals that affect brain function and development ( Morais et al, 2020 ; Chen et al, 2021 ). Recent studies detailed the associations between GM, mental health, and psychological diseases and disorders including anxiety and depression ( Kumar et al, 2023 ). Genetics, nutrition, environment, and early life experiences play a role in mental health and development via GM.…”
Section: Gut-brain Communicationmentioning
confidence: 99%
“…Additionally, it has been claimed that inflammatory states are linked to diseases like depression and anxiety. The GBA is thought to be responsible for this phenomenon ( Kumar et al, 2023 ).…”
Section: Role Of Probiotics In Gut Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the intestinal microbiome on the nervous system are usually multifaceted and include its effect on the sensory nerve fibres, including the vagus nerve, which mediate transmission of information to the CNS and decrease the perception of visceral pain (Wang and Kasper 2014 ; Moloney et al 2016 ; Mitrea et al 2022 ). Interestingly, disturbances in the intestinal microbiome can also be associated with mood disorders, depression, and anxiety, which has been demonstrated in human subjects with irritable bowel syndrome (Cryan and O’Mahony 2011 ; Kumar et al 2023 ). One of the strategies currently promoted for restoring the microbiological balance of the intestines is diet supplementation with probiotics containing selected strains of various microbial species (Hemarajata and Versalovic 2013 ).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, there is increasing evidence that the microbial community of the entire gastrointestinal tract (gut microbiota) is related to depressive disorders [30]. Multiple lines of evidence suggest that the gut microbiota is participating in the progression of obesity and related co-morbidities [30][31][32][33][34][35][36]. The neuroplasticity hypothesis, suggesting that the antidepressant effect can be regulated by modulating synaptic plasticity in hippocampal neurons and thus affecting structural plasticity in neural networks, is also the hypothesis applied in the study of the rapid antidepressant effect of ketamine [21,37].…”
Section: Introductionmentioning
confidence: 99%